2010
DOI: 10.1200/jco.2010.28.4026
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Efficacy of Methylphenidate in Enhancing Attention Regulation, Social Skills, and Academic Abilities of Childhood Cancer Survivors

Abstract: A B S T R A C T PurposeMethylphenidate (MPH) ameliorates attention problems experienced by some cancer survivors in the short term, but its long-term efficacy is unproven. Patients and MethodsThis study investigates the long-term effectiveness of maintenance doses of MPH in survivors of childhood brain tumors (n ϭ 35) and acute lymphoblastic leukemia (n ϭ 33) participating in a 12-month MPH trial. [CBCL]) were administered at premedication baseline and at the end of the MPH trial while on medication. A cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(76 citation statements)
references
References 27 publications
1
73
0
Order By: Relevance
“…Interventions aimed at improving attention and processing speed should consider lapses of attention among primary outcomes. Pharmacologic stimulant treatment has proven to effectively decrease lapses of attention in children with ADHD 34 and pediatric cancer survivors, 35 possibly providing a promising treatment of children with TBI as well. …”
Section: Discussionmentioning
confidence: 99%
“…Interventions aimed at improving attention and processing speed should consider lapses of attention among primary outcomes. Pharmacologic stimulant treatment has proven to effectively decrease lapses of attention in children with ADHD 34 and pediatric cancer survivors, 35 possibly providing a promising treatment of children with TBI as well. …”
Section: Discussionmentioning
confidence: 99%
“…58 Thus appropriate monitoring of neurocognitive function and intervening when impairments are detected are key to mitigating the long-term effect of cancer therapy in this patient population. Pharmacological and nonpharmacological interventions for remediating problems in working memory, 49 attention, 59,60 and executive function 61,62 continue to be investigated and show promise for the future.…”
Section: Org Frommentioning
confidence: 99%
“…Additionally, there has been little practical research on the design of interventions to address the poor educational outcomes commonly observed among pediatric medulloblastoma survivors. Studies of computerized and medication-based interventions have shown no significant effects on academic achievement among survivors of childhood cancer (e.g., Butler & Copeland, 2002;Butler & Mulhern, 2005;Conklin et al, 2010).…”
Section: The Present Studymentioning
confidence: 99%